CROSS-CULTURAL UNDERSTANDING AND ENGLISH COMMUNICATION QUALITY IN F&B SERVICE EDUCATION - I Gede Astawa; Eka Anastasia Wijaya (LEMBAGA PENELITIAN DAN PENGABDIAN KEPADA MASYARAKAT AKADEMI PARIWISATA DENPASAR, 2026)
The globalization of the hospitality industry requires graduates who are not only linguistically competent but also interculturally capable. This study examines the role of cross-cultural understanding as a determinant of students’ English communication quality in Food and Beverage (F&B) service practice within hospitality education. A qualitative design was employed, involving 33 students participating in simulated restaurant service interactions. Data were collected through observation, interviews, and documentation, and analyzed thematically based on the Intercultural Communicative Competence (ICC) framework.The findings reveal that although most students demonstrate basic English proficiency, only a few exhibit adequate cross-cultural understanding. Key issues include overly direct language use, inappropriate forms of address, weak politeness strategies, and first language interference. In contrast, students with higher intercultural awareness are better able to use context-appropriate language, maintain politeness, and adapt their communication effectively in service interactions. These findings confirm that cross-cultural understanding significantly influences communication quality, extending beyond linguistic accuracy to include cultural appropriateness and interactional competence. Therefore, integrating intercultural aspects into language instruction and vocational training in hospitality education is essential to better prepare students for communication in global service environments.